Making success: What does large-scale integration of making into a middle and high school look like?. (July 2019) - Trahan, Keith; Romero, Stephanie Maietta; Ramos, Renata de Almeida; Zollars, Jeffrey; Tananis, Cynthia
Making is a movement present in the United States which fosters creativity and invention through the creation and sharing of products. This case study of one Western Pennsylvania school district's integration of Making into its lower and upper secondary schools shows how the investment in space and equipment, guided by visionary leadership, can bring about innovation. Our findings after year 1 of this 2-year project indicate that Elizabeth Forward School District has been successful in fostering an atmosphere where students and teachers are given permission to fail, thereby allowing for experimentation, exploration, and the integration of girls into this normally male-dominated field.